Analysis of Fast-track Projects in the Public Sector in the United Arab Emirates - Alsuwaidi, Mariam (2025)
A Master of Science thesis in Engineering Systems Management by Mariam Alsuwaidi entitled, “Analysis of Fast-track Projects in the Public Sector in the United Arab Emirates”, submitted in April 2025. Thesis advisor is Dr. Abdulrahim Shamayleh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).